Mechanical properties of friction stir welded AL 6061-T6: influence of welding parameters and tool geometries - Armansyah; Tabatabaei, Sayed Mohamadbagher; Rostami, Seyyed Ali Latifi; Khoshnawd, Fuad; Kolahdooz, Amin; Ferdyanto; Cheng, Yee Low; Kusumah, Muhammad Afiff (UiTM Press, 2025)
Achieving strong and defect-free welds in Aluminium alloy 6061-T6 through Friction Stir Welding (FSW) remains a major materials-engineering concern. This research investigated how variations in tool form and key process parameters affect the mechanical response of the welds. Four pin geometries, including cylindrical, conical, square, and threaded-conical, were assessed through controlled experiments involving tensile testing, surface-quality inspection, and residual-stress analysis. Among the tested configurations, the square-pin tool operated at 1250 rpm with a feed rate of 125 mm min⁻¹ and a 2⁰ tilt produced the most consistent joint, reaching an ultimate tensile strength of 211.9 MPa (≈ 87 % of the base-metal strength) and a residual stress of 32 MPa within the stir zone. The results also revealed that a zero-degree tilt reduced forging pressure, leading to poor surface finish, and that the relation between feed rate and rotational speed was nonlinear. Strength increased up to an optimum level before declining. The outcomes provided a quantitative basis for selecting FSW parameters that enhanced joint integrity and extended the structural applications of Aluminium alloys.